Characterization of the Microstructure and Mechanical Properties of Austenitic Stainless Steel 304L by Utilization of Distinct Filler Materials Welded by TIG Method - Murad A. Debeski; Maryem M. Morghem; Adel M. Faraj Daw; Taher M. Alabani; Omaima M. Alkubat (African Journal of Advanced Pure and Applied Sciences, 2024)
Austenitic stainless steel is a type of steel that contains chromium and nickel. These steels are widely used in various engineering industries because they possess improved mechanical properties, especially at high temperatures. This study emphasizes the significance of utilizing different filler wire electrodes to enhance the microstructural morphologies and improve the mechanical properties of welded joints. The experimental setup involved joining AISI 304L plates with a thickness of 3mm using the Tungsten Inert Gas (TIG) metal arc welding process. Two types of electrodes, ER2209 and ER308, were employed. To analyse the chemical composition of the austenitic stainless steel plates, spectrometer analysis was conducted. This ensured the confirmation of the chemical composition of the plates before welding. The TIG welding process was carried out using a TIG machine with constant parameters of current and voltage Results: the results indicated that the microstructural investigation revealed the formation of δ-ferrite and γ-austenite in the weld (welded by ER2209 and ER308 filler). The higher δ-ferrite content was found more in ER2209 weld zone. Whereas samples welded by ER308 filler showed the columnar structure in the weld zone. Relatively, The weld joint produced with ER2209 electrodes revealed optimum UTS value and YS value of 677 and 625 in N/mm2 respectively, ER2209demonstrated better mechanical properties, while the weld joint produced with ER308 had superior ductility, also optimum hardness values of 411.9HV for HAZ and 490.72HV for Fuzion zone obtained with ER2209 electrode. Welds with both electrodes should have better mechanical properties than the base metal. The author commented that the filler wire (ER2209) exhibited better tensile properties than ER308wire due to a sufficient amount of ferrite, allotiomorphic and austenite in the form of wedge-shaped widmanstatten and as intergranular precipitates in the weld zone were found.